What Does ‘Lügenpresse’ Mean? Expressions of Media Distrust on PEGIDA’s Facebook Pages - Holt, Kristoffer; Haller, André (Politik, 2017)
The recent rise to prominence of populist politicians and movements throughout the West is often explained with reference to popular dissatisfaction with “the elite” (Mudde 2004), r. e. politicians estranged from the people they represent or journalists representing the establishment rather than acting as watchdogs of those in power. Lacking in such explanations is often a substantial account for the reasons behind popular dissatisfaction. In this article, we analyze the protest movement PEGIDA’s criticism of the press (i. e. “Lügenpresse”, the “liar press”) on Facebook. What are the main points of criticism of the press and what are the reasons expressed for this criticism, and how do they refer to traditional media in the postings? We conduct a qualitative content analysis of PEGIDA’s Facebook pages in Germany, Austria, Sweden and Norway. The focus lies on postings referring to mainstream media. The study shows that there are two main types of references: affirmative references to prove one’s own positions and contesting references which comprise media criticism.